"New Trach Mom Here…": A qualitative study of internet‐based resources by caregivers of children with tracheostomy. Issue 7 (15th March 2021) - Meyer‐Macaulay, Colin B.; Graham, Robert J.; Williams, David; Dorste, Anna; Teele, Sarah A.
Abstract: Objective: Decision‐making around tracheostomy placement and chronic respiratory support in children is complicated. Families often seek support and advice from outside the medical care team, including from social media. We undertook this study to characterize the content and nature of online resources created and managed primarily by caregivers of children living with tracheostomy and chronic mechanical ventilation. Design/Setting: We used a "grey literature" search methodology to identify internet resources created by caregivers of children with tracheostomy. We included only publicly available, nonindustry associated, English language, North American websites updated at least once in 2019. We then applied inductive content analysis to establish central themes, patterns and associations. Measurements/Main Results: We identified six blogs/forums that met our search criteria. We identified four main themes: (1) Uncertainty, (2) Lived experience—wants, needs, and emotions, (3) Seeking context and meaning, and (4) Advice/information sharing/support. Two patterns of coping were identified on the basis of the relationships between codes. The " Acceptance pathway " is associated with a sense of self‐actualization, mastery, satisfaction, return to normalcy, and ultimately acceptance. The " Resignation pathway " is associated with a sense of lack of control, frustration, burnout and stress, persistent lack of normalcy, and resignation to the tracheostomy as a negative but necessary outcome. Conclusion: Caregivers often come to see themselves as experts in the care of children with tracheostomy, though many still express ambivalence about their knowledge and skills. Those early in the experience express a desire for community and can potentially benefit from online resources.